History of philosophy as foundation for the Soviet canon: the first lecture course in dialectical materialism in Belarus in the 1920s - Dudchik, Andrei Y. (Journal of the Belarusian State University. Sociology, 2019)
The research reconstructs structure, concepts and argumentation of the first Soviet course in dialectical materialism taught and published in the 1920s in Minsk by professor S. Y. Wolfson. The analysis explicates that the course is rather heterogeneous and combines elements of different philosophical, scientific, ideological discourses. The importance of the parts in history of philosophy for the develiopment of early Soviet philosophical canon is proved.
Keywords: S. Wolfson; dialectical materialism; Soviet philosophy; Soviet philosophical canon; history of philosophy; knowledge transfer